THE INFLUENCE OF THE TRADITIONAL MARKET IMAGE ON THE SUCCESS OF SOLO CITY BRANDING - S P Putri (TATALOKA, 2019)
The positive image of the city plays a strong role in determining the success of city branding. The positive image of the city makes it easier to form competitive advantages. These city images can be communicated in various ways, and one of them through culture. This research was conducted to determine the influence of the image of traditional markets as a part of the culture of Solo in attracting residents and tourists to stay and visit. Multiple linear regression is used to test and find traditional market image factors that influence the success of city branding. The study used 120 samples consisting of residents and tourists. Sampling uses the combined sampling method. The results of the study show that there is an influence between the traditional market image on the success of city branding. Traditional markets have been proven to be able to influence the formation of a positive image of Solo although it is not the only determinant of the success of city branding. Traditional market condition and traditional market reputation are significant factors in attracting residents and tourists to stay and visit Solo.